PENGARUH SOFTWARE GEOGEBRA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI FUNGSI KUADRAT KELAS X MA SARJI AR-RASYID SITUBONDO - Ika Irmawati; Lisma Dian Kartika Sari; Tri Astindari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2020)
The purpose of this study was to determine the effect of using Geogebra software on student learning outcomes on the quadratic function material in Class X MA Sarji Ar-Rasyid Situbondo. The research method used a quasi-experimental research design with data collection techniques used, namely pretest and posttest. The data analysis technique used the normality test, homogeneity test, and t-test. From the t-test analysis, results obtained sig 0.263> É‘ 0.05. So it can be concluded that there is no significant effect between students taught by learning GeoGebra software with conventional learning. This result is due to students' low ability and experience in using Geogebra software for mathematics learning.